The Study of the Ethnic History of the Peoples of the Ferghana Valley at the Beginning of the 19th-20th Centuries (Zien Journal of Social Sciences and Humanities, 2023)
This article describes the study of the history and ethnography of the peoples who lived in the Ferghana Valley in the early 19th-20th centuries based on the research of researchers.